Ordering of mutations in acute myeloid leukemia with partial tandem duplication of MLL (MLL-PTD) - Sun, Q-Y (Leukemia, 2017)
Partial tandem duplication of MLL (MLL-PTD) characterizes acute myeloid leukemia (AML) patients often with a poor prognosis. To understand the order of occurrence of MLL-PTD in relation to other major AML mutations and to identify novel mutations that may be present in this unique AML molecular subtype, exome and targeted sequencing was performed on 85 MLL-PTD AML samples using HiSeq-2000. Genes involved in the cohesin complex (STAG2), a splicing factor (U2AF1) and a poorly studied gene, MGA were recurrently mutated, whereas NPM1, one of the most frequently mutated AML gene, was not mutated in MLL-PTD patients. Interestingly, clonality analysis suggests that IDH2/1, DNMT3A, U2AF1 and TET2 mutations are clonal and occur early, and MLL-PTD likely arises after these initial mutations. Conversely, proliferative mutations (FLT3, RAS), typically appear later, are largely subclonal and tend to be unstable. This study provides important insights for understanding the relative importance of different mutations for defining a targeted therapeutic strategy for MLL-PTD AML patients.